Glyco-engineering Using Pneumococcal Exoglycosidases: A Pilot Study on Deglycosylation of Human Alpha-1-Acid Glycoprotein (International Journal of Scientific Research in Science and Technology, 2025)
Glyco-engineering is an emerging field that focuses on modifying glycan structures to enhance or alter biological functions. Enzymatic glycan remodeling has numerous applications in biopharmaceuticals, vaccine development, and glycan-based diagnostics. Pneumococcal exoglycosidases, such as neuraminidase NanA and β-galactosidase BgaA, selectively hydrolyze terminal sugars from glycoconjugates, making them potential tools for glyco-engineering. However, their ability to modify human glycoproteins in vitro remains largely unexplored. In this study, we assessed the glyco-engineering potential of pneumococcal exoglycosidases by examining their role in deglycosylating human alpha-1-acid glycoprotein (AGP), a plasma glycoprotein involved in inflammation. Our results demonstrate that NanA removes terminal sialic acid residues from AGP, enabling subsequent galactose removal by BgaA, as confirmed by SDS-PAGE and lectin blot analysis. These findings provide experimental evidence supporting the utility of pneumococcal glycosidases for enzymatic glyco-engineering.